Imaging Reservoir Properties of the Loppa High, Norwegian Barents Sea. Examples from Alta Discovery - Hansen, Bjørn Erik (2019)
A large volume of Norway’s undiscovered hydrocarbon resources lies in the Norwegian Barents Sea. Even though exploration began in the Norwegian Barents Sea as early as 1980, the development of hydrocarbon fields has been very slow. So far only two fields (Snøhvit and Goliat) are in production in the Norwegian Barents Sea. The area has been proven to be challenging due to multiple uplift, erosion and subsidence events. Despite several challenges, the success rate in the Norwegian Barents Sea is considered high compared to the extensively explored North Sea and the Norwegian Sea. This study focuses on the reservoir characterization of Carboniferous-Permian carbonates and Triassic conglomerates located in Loppa High, southwestern Barents Sea. The reservoir characterization workflow utilizes two separate but closely linked techniques such as petrophysical analysis and rock physics diagnostics. The well log data in this study are from exploration/- appraisal wells (7220/11-1, 7220/11-2, 7220/11-3, 7120/2-1 and 7121/1-1) located within the Alta Discovery. The Carboniferous-Permian succession comprises the Falk- and Ørn Formations within the Gipsdalen Group. The reservoir units lies up-dip towards the crest of Loppa High and consist of karstified carbonates mixed with clastic sediments. The petrophysical results suggests good reservoir quality in the Carboniferous-Permian successions. Within the Alta Discovery (7220/11-1), Falk Formation has an average porosity of 12%, water saturation of 34% (66% hydrocarbons) and shale volume of 12%. The results from Ørn Formation within Alta Appraisal 3 (7220/11-3) are slightly better: average water saturation is 19% (81% hydrocarbons), porosity calculated up to 20% and the formation consists of very low shale volume (2 %). The high porosity is interpreted as a result of secondary processes such as karstification and vugs. The pay zone is estimated to approximately 21m in Falk Formation and 55m in Ørn Formation. The reservoir zone with the conglomeratic unit in Alta 2 (Appraisal, 7220/11-2) was deposited during the Triassic uplift of the Loppa High. The composition of the conglomerate is presumably eroded material from the underlying Paleozoic Falk- and Ørn Formations, characterized by unusually high density and sonic velocity. The undifferentiated formation is situated at the western flank of the Loppa High and comprises a 90m gross reservoir interval. The estimated porosity of the succession is 14% with low water saturation (11% water and 89% hydrocarbons). Similar conglomeratic units are identified above Falk- and Ørn Formations in Alta Discovery (7220/11-1) and Alta 3 (Appraisal, 7220/11-3). The hydrocarbon columns within the carbonates (Falk- and Ørn Formations) extends upwards into the conglomeratic succession with thickness of 17 and 25m respectively. Rock physics diagnostics are utilized in order to quality control the petrophysical data and to establish trends within the reservoir zones. This includes Vp vs. Vs , Vp vs. porosity ( ), Vp=Vs vs. acoustic impedance and Lambda-Mu versus MuRho crossplots. The crossplots help to establish fluid effects and lithology trends. Velocity versus porosity has been employed to characterize the pore types within the carbonate reservoir. Pore types are classified as either cracked (fractures) or stiffer pores (vugs) and characterizes the potential for hydrocarbon flow within the carbonate reservoir. Even though half of the world’s hydrocarbon resources lies within carbonate reservoirs, it is rather uncommon on the Norwegian Continental Shelf. This study has characterized the carbonates in Ørn- and Falk Formations. The results suggest the carbonates of Carboniferous- Permian have reservoir qualities for petroleum production. Plays and carbonates within the Norwegian Barents Sea is however not fully understood, further research should set focus on these issues.